Placental pathology and neonatal encephalopathy. Issue 1 (3rd July 2022) - Fox, Aine; Doyle, Emma; Geary, Michael; Hayes, Breda
Abstract: Neonatal encephalopathy (NE) is an important cause of neonatal morbidity and mortality worldwide; however, there remain gaps in our knowledge about its pathogenesis. The placenta has been implicated in the pathogenesis of this disease but conclusive evidence related to the placental factors that influence it is sparse. This review aims to outline the current knowledge on the role of the placenta with particular attention to its role in NE as a consequence of hypoxia‐ischemia. A total of 26 original articles/review papers were used to compile this review. Three themes were identified from these publications: fetal vascular malperfusion including umbilical cord pathology, inflammatory changes in the placenta, and maternal vascular malperfusion including placental weight. These features were identified as being significant in the development of NE. Advancing our understanding of this relationship between placental pathology and NE may facilitate the development of additional antenatal screening to better identify at‐risk fetuses. We highlight areas for further research through antenatal screening and placental histology. Synopsis: This article examines the association between neonatal encephalopathy and placental pathology. It highlights the specific pathology implicated in the pathogenesis of neonatal encephalopathy.